Siphula paramensis V. Marcano & L. Castillo (Icmadophilaceae, Lichenized Fungi), a new species from the high paramo in Venezuela - Marcano, Vicente (Phytotaxa, 2021)
A new species of the genus Siphula is described from the Cordillera de Merida and Sierra La Culata in the Venezuelan Andes: Siphula paramensis V. Marcano & L. Castillo sp. nov. This species closely resembles Siphula subsimplex V. Marcano from the Guayana Highlands. Siphula paramensis differs by its very small thallus, obovoid or globuliform lobes, ochre-coloured, yellowish or whitish gray (in older thalli) surface, rugose, rounded and entire apices having usually reticulated lines, less thick cortex and shorter rhizines; the thalli are K–, C+ yellow, and P+ yellow in the cortex, and contain baeomycesic and squamatic acids. This is the Siphula species that grows at the highest altitude in Venezuela. It is considered to be endemic to the Venezuelan Andes.